Arthroscopic Characterization of Syndesmotic Instability: Exactly What Measurement Matters?. Issue 2 (10th April 2018) - Abdelaziz, Mohamed; Massri-Pugin, Jafet; Lubberts, Bart; Vopat, Bryan; Guss, Daniel; Hosseini, Ali; DiGiovanni, Christopher; Johnson, Anne Holly
Category: Arthroscopy, Sports, Trauma, Other, Syndesmosis Introduction/Purpose: Ankle arthroscopy is increasingly used to diagnose syndesmostic instability by visualizing the distal tibiofibular articulation and applying a lateral fibular stress. Precisely where in the incisura one should measure potential diastasis, however, remains unclear. The purpose of this study was to determine where within the incisura one should assess coronal plane instability in purely ligamentous syndesmotic injuries when performing a lateral hook stress test (LHT). Methods: Twenty-two above-knee cadaveric specimens underwent ankle arthroscopy, first with intact ligaments and thereafter after each sequential step of syndesmotic and deltoid ligament transection. At each step, a standard 100 N hook test was applied through a lateral incision 5 cm proximal to the ankle joint and the coronal plane diastasis in the stressed and unstressed states were measured at both anterior and posterior third of the distal tibiofibular joint using calibrated probes ranged from 0.1 to 6.0 mm, with 0.1 mm of increments. Results: Anterior third diastasis did not change significantly when applying a LHT, neither in the intact state nor after any stage of ligament transection (P values ranging from p=0.61 to p=0.94). In contrast, posterior third diastasis increased significantly by applying stress at the intact state at the following stages of transection: posterior-inferior tibiofibular ligament (PITFL), PITFL plus interosseous ligament, all syndesmosis ligaments, and all syndesmosis ligaments plus superficial and deep deltoid ligament (P values ranging p=0.001 to p=0.031). Interobserver agreement was substantial (ICC = 0.81; 95% confidence interval, 0.44-0.92), and moderate (ICC = 0.73; 95% confidence interval, 0.36-0.87) for anterior and posterior third diastasis measurements, respectively. Conclusion: Syndesmotic ligament injury results in coronal plane instability of the distal tibiofibular articulation that is readily identified arthroscopically with a LHT and when measured in the posterior third of the incisura. Measurement at the anterior third of the incisura may miss such injuries.